The Effects of Ketapang (Terminalia catappa) Bark Crude Extract on Inhibition of Aeromonas hydrophila Growth and Blood Cells of the Infected Carp (Cyprinus carpio) - ., Maftuch; Suprastyani, Heny; Sanoesi, Ellana; Agus Andika Kresna Putra, Gede; Ferdian Putra, Mirsa (International Journal of Engineering and Technology, 2019)
Research aimed to determine the effect of ketapang (Terminalia catappa) bark crude extract (KBCE) on inhibition of Aeromonas hydrophila growth and blood cells of the infected carp (Cyprinus carpio). Research was conducted by completely randomized design for both in vitro and in vivo. There were four (750, 850, 950, and 1,050 ppm) and three treatments (730, 750, and 770 ppm) were used for in vitro and in vivo experiments respectively. Both experiments were replicated three times. Diameter of inhibitory zone on A. hydrophila growth was main variable in experiments. Data were analyzed by analysis of variation (and LSD. based on in vitro, 750, 850, 950 and 1,050 ppm KBCE produced the average inhibitory zone diameter of 8.97, 10.21, 11.69 and 13.89 mm respectively.Â On in vivo, erythrocytes were 224.67x10, 332.67x10, and 417.00x10 cells/mm for 730, 750 and 770 ppm KBCE respectively. In case of leukocytes were 735.89x10, 684.78x10, and 652.67x10 cell/mm for 730, 750 and 770 ppm KBCE respectively. In addition, based on measurement of water quality, water had 24.0 â€“ 25.9ï‚°C of temperature, 7.0 â€“ 7.7 of pH, and 3.9 â€“ 4.8 mg/L of DO.Â Â